2018
DOI: 10.1016/j.jvir.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolization of Hepatocellular Carcinoma with Drug-Eluting Polyethylene Glycol Embolic Agents: Single-Center Retrospective Analysis in 302 Patients

Abstract: Chemoembolization with PEG embolic agents for HCC is safe and effective, achieving an objective response rate of 85.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
(22 reference statements)
4
9
0
Order By: Relevance
“…In the non-B-TACE arm, the CR results of 41.8% in the present study are similar to those of the most recent series which reported CR rates ranging from 45 to 68% after 1- [42] and 63.2% [40] after DEM-TACE. In the B-TACE arm, the OR results of 90.1% in the present study were in line with the best responses in the literature and mirror those of three recent small series of Lucatelli et al [33], Goldman et al [46] and Bucalau et al [47] regarding B-TACE.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the non-B-TACE arm, the CR results of 41.8% in the present study are similar to those of the most recent series which reported CR rates ranging from 45 to 68% after 1- [42] and 63.2% [40] after DEM-TACE. In the B-TACE arm, the OR results of 90.1% in the present study were in line with the best responses in the literature and mirror those of three recent small series of Lucatelli et al [33], Goldman et al [46] and Bucalau et al [47] regarding B-TACE.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the non-B-TACE arm objective responses, the OR results of 86.8% using PSM in the present study are similar those reported after DEM-TACE by De Baere et al [ 38 ] in 97 patients (OR: 81%), by Aliberti et al [ 39 ] in 421 patients and by Veloso Gomes et al [ 40 ] in 302 patients after small-bead DEM TACE (OR 94.5% at 3 months and OR 85.5% at 1 month, respectively). The present results are far higher than those of Casadaban et al [ 41 ] in 188 patients treated with cTACE (OR 66%) and of Roth et al [ 42 ] in 90 patients after cTACE (OR 76.7% with doxorubicin and 73.3% with idarubicin), and are better than Richter et al [ 43 ] in the Miracle DEM-TACE study in 25 patients (OR 67%), and Guiu et al with Idarubicin-loaded DEM-TACE with 46 study participants having an OR of 68% [ 44 ] and 72 patients having an OR of 65% [ 45 ].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the BCLC stage system, TACE is recommended for patients with HCC with BCLC stage B [6, 3032]. In patients with stage C, TACE therapy is also a frequent and important application treatment, especially in comprehensive treatment [3335]. Recent studies revealed that the therapy response at first chemoembolization is a good predictor for the favorable outcome in hepatocellular carcinoma [10, 36].…”
Section: Discussionmentioning
confidence: 99%
“…They also frequently may reach the liver capsule, causing an increased risk of rupture and bleeding into the peritoneum. Furthermore, large tumors frequently also need to be treated with higher volumes of embolics and higher dosages of chemotherapy, and this inevitably rises the risk of hepatic failure and severe post-embolization syndrome (PES) [68,69]. Additionally, when considering location, tumors adjacent to the gallbladder may be vascularized by arterial branches of the cystic artery, or reflux of embolic material may reach the gallbladder, leading to cholecystitis.…”
Section: Intra-arterial: Chemoembolizationmentioning
confidence: 99%